One by one - Ware, Ruth (New York Scout Press, 2020)
"The #1 New York Times bestselling author of The Turn of the Key and In a Dark Dark Wood returns with another suspenseful thriller set on a snow-covered mountain"--
"When an off-site company retreat meant to promote mindfulness and collaboration goes utterly wrong when an avalanche hits, the corporate food chain becomes irrelevant and survival trumps togetherness. Come Monday morning, how many members short will the team be?" -- goodreads.com.
Getting snowed in at a rustic mountain chalet in the French Alps doesn't sound like the worst problem in the world. There is a breathtaking vista, a cozy fire, and company to keep you warm. But what happens when that company is eight of your coworkers-- and you can't trust any of them? When an off-site company retreat meant to promote mindfulness and collaboration is stranded by an avalanche, the corporate food chain becomes irrelevant and survival trumps togetherness. Come Monday morning, how many members short will the team be? -- adapted from jacket
108257
Keywords: Employees -- Fiction; Management retreats -- Fiction; Disasters -- Avalanches -- Fiction; Avalanches -- Fiction; Murder -- Fiction; High technology industries -- Fiction; Survival -- Fiction; Fiction / Thrillers / Psychological; Fiction / Thrillers / Suspense; Fiction / Literary; Alps, French (France) -- Fiction; Fiction; Thrillers (Fiction); Suspense fiction